Microvascular abnormalities secondary to radiation therapy in neovascular age-related macular degeneration: findings from the INTREPID clinical trial. Issue 4 (21st June 2018) - Freiberg, Florentina Joyce; Michels, Stephan; Muldrew, Alyson; Slakter, Jason; O'Shaughnessy, Denis; Czeszynski, Alan; Danielson, Linda; Jackson, Timothy L; Chakravarthy, Usha
Abstract : Purpose: To report the incidence and features of retinal microvascular abnormalities (MVAs) occurring secondary to stereotactic radiotherapy (SRT) in a randomised double-masked sham-controlled clinical trial at 21 European sites. Methods: Two hundred and thirty participants with neovascular age-related macular degeneration (AMD) treated with at least three intravitreal antivascular endothelial growth factor (anti-VEGF) injections prior to enrolment, and demonstrating a continuing need for re-treatment. Interventions: 16 Gy, 24 Gy or sham SRT. All three groups received pro re nata anti-VEGF injections if the lesion was judged to be active at review visits. Colour fundus images from baseline and 6 months and fluorescein angiograms from baseline and annual visits were graded for measures of morphological outcome and safety using a prespecified protocol with accompanying definitions to distinguish RT-related MVA from non-specific retinal vessel abnormalities that are known to occur in neovascular AMD. The main outcome measure was MVA detected by months 12, 24 and 36 after enrolment. Results: The frequency of MVAs in the combined SRT arms was 0% in year 1, 13.1% in year 2 and 30.3% in year 3. The area of MVA was small and the mean change in visual acuity in year 2 was similar in a subset of SRT eyes with MVAs, versus those without MVAs. MVA was considered to have possibly contributed to vision loss in 2 of 18 cases with MVA in year 2, and 5 of 37 cases in year 3. Conclusion: Treatment with SRT is associated with development of subtle MVAs that have little or no impact on visual outcome. These findings can help clinicians recognise the retinal MVAs that occur in response to SRT.